Mapping stem cell activities in the feather follicle - Yue, Zhicao (Nature, 2005)
It is important to know how different organs ‘manage’ their stem cells. Both hair and feather follicles show robust regenerative powers that episodically renew the epithelial organ. However, the evolution of feathers (from reptiles to birds) and hairs (from reptiles to mammals) are independent events and their follicular structures result from convergent evolution. Because feathers do not have the anatomical equivalent of a hair follicle bulge, we are interested in determining where their stem cells are localized. By applying long-term label retention(1), transplantation(2) and DiI tracing to map stem cell activities, here we show that feather follicles contain slow-cycling long-term label-retaining cells (LRCs), transient amplifying cells and differentiating keratinocytes. Each population, located in anatomically distinct regions, undergoes dynamic homeostasis during the feather cycle. In the growing follicle, LRCs are enriched in a ‘collar bulge’ niche. In the moulting follicle, LRCs shift to populate a papillar ectoderm niche near the dermal papilla. On transplantation, LRCs show multi-potentiality. In a three-dimensional view, LRCs are configured as a ring that is horizontally placed in radially symmetric feathers but tilted in bilaterally symmetric feathers. The changing topology of stem cell activities may contribute to the construction of complex feather forms.